Students’ learning activeness in studying Islamic religious education: How does it relate to their learning independence? - Naista Fabela Sari; Baharudin Baharudin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study investigates the correlation between learning independence and active participation among students in Islamic Religious Education (IRE) at MAN 2 Bandar Lampung. Preliminary observations showed that only 15% of students demonstrated adequate self-confidence in independent learning, while responsiveness to questions reached merely 12%, indicating reduced engagement and growing reliance on AI during learning activities. Using a quantitative correlational design with an ex-post facto approach, the study involved 160 students selected through simple random sampling. Data were collected using a Likert-scale questionnaire. The findings show a significant positive relationship between learning independence particularly students’ self-confidence and their responsiveness in classroom learning. These results underscore the importance of strengthening students’ confidence in autonomous learning as a primary strategy to enhance classroom responsiveness. Educators are encouraged to implement approaches that intentionally build self-confidence to improve active participation in IRE learning.